The influence of students' environment on students' learning motivation - feby kurniawan; Yeni Erita; Didi Syahrir; Vani Qhairum Nisa Utami (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
This research uses a qualitative approach and a literature study. The purpose of this study was to analyze the influence of the student learning environment on students' learning motivation. The researcher collected data from this study by collecting and reviewing consistent data from previous researchers. The result of this study is the influence of the environment. The environment greatly impacts the development of students starting from the enthusiasm for learning, values, ​​and even the personality of students where the student environment consists of the family environment, community, school, and friend environment where all of these things can support student achievement and attitudes in receiving learning, the environment is part of the support so that learning can run well and get maximum results.